Grebe Syndrome - Case Report With Review of Literature - Nagaraj, Rashmi; Kiran, HS (Journal of Nepal Paediatric Society, 2021)
Grebe syndrome is a rare genetic condition characterized by short limb dwarfism. It is transmitted by autosomal mode of inheritance. There are no associated anomalies and the affected child has normal intelligence and normal life span. This syndrome has a very low incidence and needs to be differentiated from other forms of short limb dwarfism since treatment options may vary. We have described here a severely affected case of the same with review of literature.